Analisis Penerapan Profil Pelajar Pancasila Dimensi Kebhinekaan Global Pembelajaran IPAS Kelas 4 SDN Ciracas 06 - Kusumastuti, Ananda Mei; Wati, Dita Prihatna (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research aims to analyze the application of Pancasila in the context of global diversity and to determine the factors that hinder the application of the Pancasila profile in science and science learning. Using qualitative descriptive research methods with data collection techniques in the form of observation, interviews and documentation. With class IV students and teachers as research subjects. for data analysis. This method consists of three important stages: data reduction, data exposure, and formulation of conclusions. The results of the research show that science and science learning encourage the development of four-dimensional elements, namely recognizing and appreciating culture, communication and interaction between cultures, reflection on responsibility and social justice. However, the learning process is not yet optimal due to obstacles such as limited teacher ability to design effective teaching modules and lack of infrastructure. This research hopes that students can improve and implement the character of global diversity in everyday life. Teachers must try to be role models for the school community and approach students to overcome existing obstacles and problems. To achieve the expected learning objectives, teachers can also replace limited infrastructure with simpler learning media.